Rats’ preferences for high fructose corn syrup vs. sucrose and sugar mixtures - Ackroff, Karen (2011)
High fructose corn syrup (HFCS) has replaced sucrose in many food products, which has prompted research comparing these two sweeteners in rodents. The present study examined the relative palatability of HFCS and sucrose for rats, offering 11% carbohydrate solutions to match the content of common beverages for human consumption. The animals initially preferred HFCS to sucrose but after separate experience with each solution they switched to sucrose preference. Approximating the composition of HFCS with a mixture of fructose and glucose (55:45) yielded a solution that was less attractive than sucrose or HFCS. However, HFCS contains a small amount of glucose polymers, which are very attractive to rats. A 55:42:3 mixture of fructose, glucose and glucose polymers (Polycose) was equally preferred to HFCS and was treated similarly to HFCS in comparisons vs. sucrose. Post-oral effects of sucrose, which is 50% fructose and 50% glucose, may be responsible for the shift in preference with experience. This shift, and the relatively small magnitude of differences in preference for HFCS and sucrose, suggest that palatability factors probably do not contribute to any possible difference in weight gain responses to these sweeteners.